Techno-Economic Analysis of Retrofitted Electric Coaster Introduction in University Campus - Rahman, Mohammed Ataur; Sany, Ihsan; Ahmad, Faris Ismail (B.P International, 2021)
Green transportation concentrates around resource efficiency and effectiveness, resulting in a lower carbon and healthier environment for the nation through lowering greenhouse gas emissions. Promising novel technologies may be the ultimate solution, but innovation will only happen if society plays a key role in the development of electric vehicles aimed at reducing carbon emissions. Understanding how markets work to save fuel is necessary for developing successful and affordable policies to enable the implementation of low-carbon technologies in accordance with political goals. The goal of this research is to construct an all-electric mini-coaster (14 seats) by retrofitting a diesel engine Mercedes Benz Van with a 15 kWh lithium-iron-phosphate battery (LiFePO4). The coaster is propelled by an AC induction motor with a peak power of 60 kW and torque of 150 Nm. A 3.44 kWh lithium battery has also been employed as an auxiliary battery to run the battery cooling system and passenger compartment cooling system. With a single fully charged battery, the coaster can ride 40 kilometers. The coaster's power consumption is 340 Wh/km [cost USD 0.025 (RM0.12) per km] depending on Malaysian gasoline prices. The coaster's real operating cost is RM144 per month when powered by a battery, and RM600 per month when powered by an internal combustion engine. As a result, the cost-effective electric mini-coater benefits both the International Islamic University of Malaysia (IIUM) and the environment.